Vehicle sprung mass estimation for rough terrain. (6th December 2012) - Pence, Benjamin; Hays, Joseph; Fathy, Hosam K.; Sandu, Corina; Stein, Jeffrey
This paper provides methods and experimental results for recursively estimating the sprung mass of a vehicle driving on rough terrain. A base-excitation model of vertical ride dynamics treats the unsprung vertical accelerations, instead of the terrain profile, as the input to ride dynamics. Recently developed methods based on polynomial chaos and maximum likelihood theory estimate the most likely value of the vehicle sprung mass. The polynomial chaos estimator is compared to least squares and Kalman filtering approaches. An experimental study suggests that the proposed approach provides accurate outputs and is less sensitive to tuning parameters than the benchmark algorithms.